Non-invasive fetal RHD and RHCE genotyping using real-time PCR testing of maternal plasma in RhD-negative pregnancies - Hromadnikova, Ilona; Vechetova, Lenka; Vesela, Klara; Benesova, Blanka; Doucha, Jindrich; Vlk, Radovan (The journal of histochemistry and cytochemistry, 2005)
We assessed the feasibility of fetal RHD and RHCE genotyping by analysis of DNA extracted from plasma samples of RhD-negative pregnant women using real-time PCR and primers and probes targeted toward RHD and RHCE genes. We analyzed 45 pregnant women in the 11th to 40th weeks of pregnancy and correlated the results with serological analysis of cord blood after delivery. Non-invasive prenatal fetal RHD exon 7, RHD exon 10, RHCE exon 2 (C allele), and RHCE exon 5 (E allele) genotyping analysis of maternal plasma samples was correctly performed in 45 out of 45 RhD-negative pregnant women delivering 24 RhD-, 17 RhC-, and 7 RhE-positive newborns. Detection of fetal RHD and the C and E alleles of RHCE gene from maternal plasma is highly accurate and enables implementation into clinical routine. We recommend performing fetal RHD and RHCE genotyping together with fetal sex determination in alloimmunized D-negative pregnancies at risk of hemolytic disease of the newborn. In case of D-negative fetus, amplification of another paternally inherited allele (SRY and/or RhC and/or RhE positivity) proves the presence of fetal DNA in maternal circulation.
Keywords: Blood Grouping and Crossmatching; Rh-Hr Blood-Group System; polymerázová řetězová reakce; Male; Genotype; Pregnancy; těhotenství; Prospective Studies; mužské pohlaví; fetální krev; Fetal Blood; krevní skupiny - systém Rh-Hr; určování krevní skupiny a křížové zkoušky; lidé; ženské pohlaví; Humans; genotyp; Polymerase Chain Reaction; Female; prospektivní studie